GOVERNMENT STRATEGY IN MANAGEMENT OF PARKING RETRIBUTION IN NATURAL TOURISM AREAS - Nastia Nastia; Hastuti Hastuti; L.M. Azhar Sa'ban (Jurnal Inovasi Penelitian, 2021)
South Buton Regency, as one of the tourism destinations in the Buton Islands, features a variety of tourist attractions. The government must manage parking costs in tourist areas, and every use of the budget must be transparent, so a village government strategy to turn strengths into opportunities, strategies to exploit weaknesses into opportunities, strategies to transform threats into strengths, and strategies to avoid threats is required. As a result, the goal of this research is to examine the village government's parking fee optimization technique to boost Regional Original Income. This type of study employs a qualitative approach and a descriptive approach, as well as a SWOT analysis. According to the SWOT analysis, the parking management of the Kaburaburana tourist area has been progressing well in an endeavor to boost tourism potential. However, these findings continue to present challenges or hurdles at various stages of the process.